PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN PERTUMBUHAN LABA SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2018-2020 - Luluk Anggraini; Dwi Perwitasari Wiryaningtyas; Triska Dewi Pramitasari (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Financial management is the most important management for a company. The purpose of this study was to analyze and test the effect of profitability, profit growth and firm value on food and beverage companies listed on the Indonesia Stock Exchange for the period 2018-2020. This research is quantitative descriptive. The sampling technique in this research is purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that profitability has a significant positive effect on profit growth, profitability has a significant positive effect on firm value, profit growth has a significant positive effect on firm value, profitability has a significant positive effect on firm value through profit growth.